Species-specific macroinvertebrate responses to climate and land use scenarios in a Mediterranean catchment revealed by an integrated modelling approach. (November 2020) - Sultana, Jawairia; Recknagel, Friedrich; Nguyen, Hong Hanh
Highlights: Unique combination of GF, SWAT and HEA revealed species responses to future changes. GF identified macroinvertebrate species responding strongly to key driver stream flow. Process-driven model SWAT predicts stream flow under changing climate and land use. HEA develops models to predict macroinvertebrate species for changing flow scenarios. Distinct macroinvertebrate responses highlight the need for species-specific analysis. Abstract: Climate and land use changes are altering flow and nutrient regimes in catchments that affect stream habitats and aquatic biodiversity. This study applied an integrated modelling approach to quantify the impacts of climate and land use scenarios on the macroinvertebrate community in Sixth Creek catchment, South Australia. Gradient forest (GF) determined flow as most important driver affecting macroinvertebrate assemblages, and identified most flow-sensitive species based on highest cumulative importance along flow gradients. A catchment model developed using the Soil and Water Assessment Tool (SWAT) simulated flow under the following scenarios: (1) deforestation, (2) reforestation, (3) climate change, and (4) a 10% increased urbanisation as projected by local authorities over the next 30 years. The urbanisation scenario predicted a 2% increase of average flow compared to 17% flow increase predicted by the deforestation scenario. In contrast, diminished monthly flow was suggested by both the climate change scenarios due to declining precipitation and higher temperatures, and the reforestation scenario most likely due to declining surface run-off. In reforestation and climate change scenarios, SWAT results predicted the highest decline in flow during late autumn and late spring, which may shift this unusual permanent flowing stream towards intermittency. The Hybrid Evolutionary Algorithm (HEA) was used to develop flow-driven models for population dynamics of taxa identified by GF as flow sensitive i.e. Hydrobiidae spp., Austrocerca tasmanica, Offadens spp., Cloeon spp., Micronecta spp. and Tasmanocoenis tillyardi based on 14 years of data monitored at a representative stream site of Sixth Creek. The HEA models achieved coefficients of determination r 2 between 0.85 and 0.97 for predicted vs. observed abundances. While the abundance of Cloeon spp. diminished in all scenarios, it was most affected by low flow predictions of the climate change scenario. Hydrobiidae spp. appeared most tolerant to altered flow conditions by reaching highest abundances at high flow conditions caused by deforestation and urbanisation. Overall, this study highlighted the non-linear response of species within the commonly used Ephemeroptera, Plecoptera and Trichoptera (EPT) grouping and a need to redirect focus of such studies from community to species level. The integrated modelling approach based on GF, SWAT and HEA proved to be suitable for simulating complex species-specific macroinvertebrate responses to relevant climate and land use scenarios. Learning more about these interrelationships is a prerequisite for sustainable catchment management.